A Study of Factors that Influence Intention to Use Telemedicine Applications in the Era of Post Covid-19 Pandemic in Indonesia - Hafizhul Mizana; Jenny Octavia; Maria Veronica Simanjuntak; Pradith T Wijonarko; Rita Triani (Syntax Corporation Indonesia, 2023)
This study was conducted to get some insights into what factors influence individual behavior to use telemedicine applications post-COVID-19 pandemic in Indonesia. Some studies were done previously during the COVID-19 pandemic era; however, as we moved to the new era post covid-19 pandemic, it would be interesting to find the answers. The research method was the quantitative approach. Survey to total 746 respondents spread throughout Indonesia were conducted, but 620 valid responses were collected to analyse user behavior towards the of telemedicine applications. Findings – The findings indicated that intention to use telemedicine application post COVID-19 pandemic in Indonesia was jointly predicted and explained 64.8% by performance expectancy, effort expectancy, social influence, facilitating condition, hedonic motivation, price values, habit, perceived security and reliability. The result also revealed that three variables which are performance expectancy, habit, perceived security and reliability have strong positive correlations and significant influence on individual behavior towards the use of telemedicine. Respondents were collected randomly from some areas, meanwhile Indonesia is a large country, consists of more than 10,000 islands. The result may be applicable only in some places. Based on the findings, it is important for healthcare professionals or those who have interest in the telemedicine industry to carefully look at three key factors related to improve performance expectancy, build users habit, and ensuring security and reliability in order to drive individuals' behavior to use telemedicine application in Indonesia. This study is using modified UTAUT2 model to assess individual behavior towards use of telemedicine application post covid-19 pandemic in Indonesia.